Correction to: China's health assistance to Africa: opportunism or altruism? - Shuang Lin; Liangmin Gao; Melissa Reyes; Feng Cheng; Joan Kaufman; Wafaa M. El-Sadr (BMC, 2018)
Please note that following publication of the original article [1], one of the authors has flagged that the abbreviations section lists "BRIC" as "Britain, Russia, India and China".